Narrativas de educação e resistência : a prática popular griô - Pinheiro, Cristiano Guedes (2013)
The dissertation Narratives of Education and Resistance: The Griot Popular Practice of Mrs Sirley, addresses the problem of a popular narrative as a process of education and resistance in our days. Based on the methodological assumptions of the case study, participant observation and narrative interview, the research deals with the following issue: can the practice of popular narratives, by means of a specific subject, be perceived as an educational and resistance process? In the context of this discussion, authors like Walter Benjamin, Homi Bhabha and Pedrinho Guareschi are used and read from the perspective of the Critical Pedagogy by Peter McLaren and Henry Giroux. At the end, the practice of storytelling griot is proposed as a process of education and resistance in the framework of a border pedagogy.